(untitled) (Bangladesh Journal of Medical Education, 2021)
This descriptive type of cross-sectional study was conducted to find out the views of undergraduate dental college teachers about the PowerPoint presentations as instructional media used by teachers in dental colleges of Bangladesh. The study period was from January 2018 to December 2018. The study was carried out among the teachers of all 4 phases of BDS course of 2 government and 2 non-government dental colleges of Bangladesh. Out of 4 dental colleges, 2 were within Dhaka and 2 were outside Dhaka. The sample size was 100 for teachers. Convenience sampling technique was adopted for data collection. Self-administered semi-structured questionnaires using five points Likert scale were used for collections of data from teachers. The study revealed that 72% teachers consider Eye appealing appearance for choosing PowerPoint slides and 58% teachers did not use master slide. For selection of font style, 67% teacher agreed they consider readability, 88% agreed they consider visibility from last bench of classroom to select font size but 61% teacher disagree that they consider background for selecting font color. The study recommended, during the preparation of a PowerPoint presentation by teachers some areas like using the master slide, background, the number of words and lines need attention. Bangladesh Journal of Medical Education Vol.12(1) 2021: 10-15